#20: Modeling Zika virus tissue tropism in rhesus macaques to define the risk of donor derived transmission. (28th June 2021) - Treadway, Taylor A; Shepherd, Phoenix M; Newman, Christina M; Mohr, Emma L; Dudley, Dawn M; Breitbach, Meghan E; Yamamoto, Keisuke; Stewart, Laurel M; Koenig, Michelle R; Bliss, Mason; Rybarczyk, Sierra L; Weiler, Andrea M; et al.
Abstract: Background: Almost 115, 000 people in the United States are currently on a transplant waitlist, which vastly exceeds the number of organ donors every year. This discrepancy emphasizes the need for retention of all possible donors. Those who have recently traveled to an area with an active outbreak of Zika virus (ZIKV) are often disqualified as a donor because immunosuppressed recipients would be at risk of a donor-derived ZIKV infection. Therefore, we define ZIKV tissue tropism and the risk of donor derived transmission. Methods: We subcutaneously inoculated 15 Indian-origin rhesus macaques (RM) with a Puerto Rican isolate of ZIKV (PRVABC59). All RMs were inoculated in mid to early gestation.We inoculated during pregnancy because plasma viremia is typically prolonged in pregnancy and we wanted to model tissue tropism for donor derived transmission in the worst scenario of prolonged viremia. At 30, 65, and 105 days post-infection (dpi), the animals were euthanized and comprehensive necropsies were performed, which evaluated a minimum of 60 tissues per animal. ZIKV RNA was quantified in tissues via qRT-PCR. Results: Plasma viremia duration was >10 days in 13 of 15 RMs. ZIKV RNA was most commonly detected in lymph nodes, with 19/45 lymph nodes that were vRNA positive in 5 RMs at 30 dpi. There were 15/45 vRNA positive lymph nodes at 60 dpi and 8/38 at 105 dpi. Reproductive and maternal fetal-interface (MFI) tissues were the second most commonly positive tissues. Twenty-five MFI tissues, including the amniotic/chorionic membrane, decidua, placenta, uterus, and placental bed, were positive, with 10/53 positive at 30 dpi, 14/24 positive at 60 dpi and 1/47 positive at 105 dpi. Other vRNA positive tissues included the primary bronchus, femoral vein, kidney, thyroid, lung, colon, mammary gland, pericardium, hand nerve, and sciatic nerve in 1–2 RMs at one of the three timepoints. Conclusions: We found ZIKV RNA most frequently within lymph nodes. Lymph nodes are included in lung and small bowel transplants, indicating that these transplants could pose a risk of donor-derived ZIKV transmission. Virus detection within other commonly transplanted tissues, such as the kidney and blood vessels was much less common. We did not determine what fraction of vRNA comes from replication-competent virus in each tissue; some tissues with vRNA might not contain virions that could initiate new infections. Donor-derived Zika virus transmission from other commonly transplanted organs, such as liver, seems unlikely since no viral RNA was detected in this organ.